Oxygen‐Deficient Ti0.9Nb0.1O2‐x as an Efficient Anodic Catalyst Support for PEM Water Electrolyzer. Issue 10 (25th April 2019) - Lv, Hong; Wang, Sen; Hao, Chuanpu; Zhou, Wei; Li, Jiakun; Xue, Mingzhe; Zhang, Cunman
Abstract: Herein, the low cost and efficient oxygen‐deficient Ti0.9 Nb0.1 O2‐x as support of IrO2 (noted as IrO2 /TNO) anode catalyst for the PEM water electrolyzer is synthesized and then characterized using a series of techniques. Oxygen vacancies are introduced by hydrogenation treatment. The IrO2 /TNO sample after hydrogenation (noted as IrO2 /TNO−Hx, x corresponds to the hydrogenation temperature) exhibits enhanced electronic conductivity and increased surface active sites relative to that of the pristine IrO2 /TNO sample. A single cell is assembled by IrO2 /TNO−Hx as anode catalyst, commercial Pt/C as cathode catalytic and Nafion 117 membrane as electrolyte. At a low loading mass of IrO2, the IrO2 /TNO−H750 sample shows the optimum oxygen evolution reaction (OER) activity (1.832 V at 1 A ⋅ cm −2 ), which is superior to that of unsupported IrO2 (1.858 eV at 1 A ⋅ cm −2 ), and remains stable for 100 h operating at a current density of 1 A cm −2 . This work provides a rational design strategy for developing low cost and efficient anode catalysts support. Abstract : Supporting OER : Low‐cost Ti0.9 Nb0.1 O2‐x was synthesized and used as the support of IrO2 anode catalyst for the PEM water electrolyzer. The IrO2 anode catalyst supported on Ti0.9 Nb0.1 O2‐x support exhibits excellent oxygen evolution activity and long‐term stability, which could be attributed to the enhanced electrical conductivity, increased surface active sites and a favored charge transfer reaction.